2012
DOI: 10.4103/0974-8490.99071
|View full text |Cite
|
Sign up to set email alerts
|

Sub-acute effect of NG-nitro-l-arginine methyl-ester (L-NAME) on biochemical indices ins rats: Protective effects of Kolaviron and extract of Curcuma longa L

Abstract: Background:Kolaviron (KV) (biflavonoid from Garcinia kola) and extract of Curcuma longa (CL) are frequently used in folk medicine for treatment of hypertension. One of their mechanisms of action is to enhance antioxidant properties in animals. NG- nitro- l- arginine methyl- ester (L- NAME) is L- arginine analogue, which by binding to Nitric Oxide Synthase (NOS) may induce hypertension partly due to increase in tissues oxidative stress.Objectives:To investigate the effect of L- NAME on some biochemical indices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…In the heart and kidneys however, the concentration of NO in L-NAME groups was comparable to normotensive control. This finding was consistent with previous studies by Adaramoye et al [38] and Berkban et al [39] who also observed normal levels of NO in heart and kidney of L-NAME treated rats. Abdel-Raham et al [40] proposed that eNOS protein expression may be up-regulated in L-NAME treated rats as a counter-regulatory mechanism to compensate for increased BP.…”
Section: Discussionsupporting
confidence: 93%
“…In the heart and kidneys however, the concentration of NO in L-NAME groups was comparable to normotensive control. This finding was consistent with previous studies by Adaramoye et al [38] and Berkban et al [39] who also observed normal levels of NO in heart and kidney of L-NAME treated rats. Abdel-Raham et al [40] proposed that eNOS protein expression may be up-regulated in L-NAME treated rats as a counter-regulatory mechanism to compensate for increased BP.…”
Section: Discussionsupporting
confidence: 93%
“…A strong body of evidences suggests that chronic inhibition of NOS by L-NAME alters various biochemical indices [ 59 ]. In the current study, the activities of the liver marker enzymes (ALT, AST, and γ -GT) were significantly elevated after L-NAME administration in comparison with normal controls, denoting hepatic injury ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several biochemical processes such as catalase activity and lipid peroxidation are also altered. These processes may serve as alternative pathway in the metabolism of nitric oxide [37,38]. Therefore, the restoration of antioxidant capacity due to the administration of scopoletin and tempol may induce a better blood pressure lowering effect in the oxidative stress-associated hypertensive model.…”
Section: Discussionmentioning
confidence: 99%